Preparation of simulated double curved canals with WaveOne, Reciproc and ProTaper Next system - Koprowicz, Agata; Łęski, Michał; Pawlicka, Halina (Journal of Stomatology, 2016)
Introduction. The purpose of the mechanical preparation of the root canal is to create a continuously tapering funnel form, extending from the coronal access cavity to the root apex, as well as to maintain the original canal shape and apical foramen in their original spatial relationship both to the periapical tissues and the root surface. In the case of curved canals this work is considered to be a challenge for dentists. The most common procedural errors, such as apical perforation or strip perforation, relate to the teeth with complicated root canal anatomy. Aim of the study. To evaluate the shape of canals with a double curved curvature after preparation with different instruments with respect to canal transportation, the amount of removed material from canal walls, as well as apical transportation and its diameter. Material and methods. The study involved reciprocating files, WaveOne (Dentsply Maillefer), Reciproc (VDW), and rotary ProTaper Next system (Dentsply Maillefer). Thirty resin blocks (Endo-Training-Bloc, Dentsply Maillefer) with hollow inside canals containing a double curvature (S-shaped canals) were used in the study. Blocks were photographed before and after preparation. After the superimposition of images in a computer program, measuring points were determined. The amount of the removed material corresponded to the distance between the measuring point and the wall of the canal after the preparation. To elaborate the collected data, descriptive and statistical inference methods were used. Results. This study has confirmed the scientists’ opinions that differences in the structure and working movement of files affect the resulting shape of the root canal. The tested instruments ensure simulated canal preparation in a manner which evidently deviates from expectations. The concept of one file with a high and variable taper creates the risk of more extensive canal transportation. The comparison of the preparation with the system based on a sequence of files revealed statistically significant differences. In the case of double curved canals the ProTaper Next instruments seem to be the right choice.